Identification of Lichen Based on Substrate in Bale Village, Tanantovea District, Donggala Regency - Adrian Adrian; Lilies Lilies; Lestari MP Alibasyah; Bustamin Bustamin; Syech Zainal; Musdalifah Nurdin (Biology, Medicine, & Natural Product Chemistry, 2026)
Lichens are associations between fungi and photosynthetic symbionts, such as algae or cyanobacteria, that form stable and specialized thallus structures. The fungi that predominantly compose the lichen body belong to the Ascomycetes, while the algal partners contribute to the overall structure. This association enhances the ability of both fungi and algae to survive in suboptimal environmental conditions because the thallus structure, physiology, and chemical synthesis of lichens differ from those of the individual fungi or algae that constitute them. Lichens are lower plants that occur in various habitats worldwide and dominate terrestrial ecosystems, covering approximately 8% of the Earth’s land surface. Globally, around 20,000 lichen species have been reported, whereas in Indonesia, 595 species or about 3% of the world’s total have been documented. This study aimed to identify lichen species based on their substrates in the Bale Village area, Tanantovea District, Donggala Regency. The sampling method used was the exploration method. Lichen samples were collected from various substrates, followed by direct macroscopic observations to identify the species obtained. Research sites were determined using purposive sampling, selected based on the environmental conditions and the diversity of substrates where lichens grow. Three locations were designated as research stations: Station 1 (residential area), Station 2 (forest and river area, partly used as a tourist site), and Station 3 (forest area and local plantations). The results of this study identified 10 lichen species belonging to 5 families and found on 3 types of substrates. Environmental parameter measurements at the research sites showed an average temperature of 27.66°C, air humidity of 66%, and light intensity of 828.66 cd. These values indicate warm, humid conditions with moderate to highlight intensity conditions generally optimal for the growth and development of lichens.